2019
DOI: 10.1007/s40801-019-00172-9
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Analysis of Switching Patients with Schizophrenia from Oral Risperidone or Oral Paliperidone to Once-Monthly Paliperidone Palmitate

Abstract: Purpose Reducing the dosing frequency of antipsychotics (APs) with long-acting injectables (LAIs) such as once-monthly paliperidone palmitate (PP1M) can improve adherence and clinical outcomes for schizophrenia patients. This US study compared physical and psychiatric comorbidity-related outcomes, AP adherence, healthcare resource utilization (HRU), and costs pre-and post-transition to PP1M among schizophrenia patients treated with oral risperidone/paliperidone pre-PP1M transition. Methods Health insurance cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…As expected and consistent with the previous studies [ 24 , 30 ], the mean number of outpatient visits increased significantly from pre to post PP1M initiation. PP1M treatment necessitates a physician outpatient visit each month as opposed to oral antipsychotic treatment in which routine visits are usually spaced every 3–6 months.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected and consistent with the previous studies [ 24 , 30 ], the mean number of outpatient visits increased significantly from pre to post PP1M initiation. PP1M treatment necessitates a physician outpatient visit each month as opposed to oral antipsychotic treatment in which routine visits are usually spaced every 3–6 months.…”
Section: Discussionsupporting
confidence: 92%
“…For example, in a previous study of Veteran Affairs patients transitioning from orally administered paliperidone/risperidone to PP1M, Patel et al found that the mean number of visits reduced for all-cause (2.3 to 1.5, p < 0.05), mental health-related (1.5 to 0.8, p < 0.05), and schizophrenia-related inpatient visits (0.6 to 0.3, p < 0.05) from 12 months before to 12 months after transitioning to PP1M. The mean length of stay also reduced for all-cause (28.1 to 14.0 days, p < 0.05), mental health-related (27.1 to 13.8 days, p < 0.05), and schizophrenia-related (13.2 to 5.7 days, p < 0.05) inpatient visits [ 30 ]. Other studies have compared HRU between patients on PP1M and those on oral antipsychotics and have reported reduced acute HRU in patients on PP1M compared to those on oral antipsychotics [ 23 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The once-monthly PLAI used to treat patients with acute exacerbation of schizoaffective disorder alleviated psychotic symptoms and manic and depressive symptoms [ 49 ]. Paliperidone has also been demonstrated to alleviate depressive symptoms in patients with schizophrenia [ 51 ]. In our study, the LAI group used fewer concomitant medications than did the NLAI group, including antidepressants, which suggests that PLAI can also treat depressive symptoms in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal levels of adherence and persistence with antipsychotic therapy are ongoing challenges in the treatment of schizophrenia. 1,2 As reported by the American Psychiatric Association, poor adherence is associated with poor outcomes, including increased risks of relapse, rehospitalization, suicidal and aggressive behaviors, and mortality. 2 Because of their long pharmacokinetic half-lives, longacting injectable (LAI) formulations of antipsychotic medications allow for less-frequent treatment administration and can reduce the treatment burden associated with having to remember to take a medication every day.…”
Section: Introductionmentioning
confidence: 99%